Keragaman Jenis Anggrek di Kawasan Hutan Distrik Oksibil, Pegunungan Bintang, Papua* - Verena Agustini; Supeni Sufaati; Suharno Suharno (Jurusan Biologi FMIPA Universitas Cenderawasih, 2012)
Pegunungan Bintang is one of new regencies in Papua Province which was used to be part of Jayawijaya regency. In connection with the development of a new region there are many forest areas had been converted to infrastructure development. Those conversion has adverse impact on the presence of flora and fauna including orchids in the areas. Therefore this study was done to obtain the information about the diversity of orchids species at forest area of Oksibil District, Pegunungan Bintang, Papua. The study was conducted in seven of ten villages including Oksibil as the capital city of Pegunungan Bintang. The result showed that there are 9 genera consist of 23 species of both epiphytic and terrestrial orchids. Dendrobium and Agrostophyllum are more frequently found than others. Among them only few species has been collected by the local people without proper propagation. Key words: Orchids, diversity, Oksibil, Pegunungan Bintang.